Zakho In the Perspective on Nineteenth Travelers - Ibrahim, Mohammed A. (Humanities Journal of University of Zakho, 2017)
Zakho has a strategic position in terms of connecting all parts of Great Kurdistan most importantly, it bridges south, north and west parts of it. Moreover, it was a connecting point between borders of two Kurdish emirates namely, Badinan and Botan in the era of the Ottoman Empire. It also connected Soran and Botan Emirates at the time of collapsing Emir Mohammed's rule the king of Rwandz. Flowing Khabur river through Zakho and crossing it using boats (Kalek) by Travelers also helped them to be better familiar with its natural and human phenomena. They recorded many historical events, most important is the travel of Ten thousand army of Greek Xenophon through Zakho. All these events that happened in Zakho and its surrounding areas attracted the attention of historian and Travelers, and made them give explanations about the events. Moreover, some Travelers proved the existence of Jewish community in and outside Zakho. What led to Travelers to pay attention to Zakho was. Zakho situated among Amedi, Botan, and Diyarbakir. It was also a small commercial center related to Mosul Vilayet after the collapse of Badinan Emirates and when Rashid Mohammed Pasha attacked Soran and ended the rule of Soran Emir. Generally speaking some Travelers perspectives about Zakho are recorded thoroughly and accurately. Some Travelers that visited Zakho in 19th century is Spanish diplomat (Adolf Rivedenira) British Traveler (John Asher), American Doctor and missionary (Lobdell), Henry A. Stern, Karl Baedeker, Horato Southgate, George Percy, Badger. Lieut-Col. J. Shiel a British officer.